Small Luggage for a Long Journey: Transfer of Vesicle-Enclosed Small RNA in Interspecies Communication - Lefebvre, Fabio A.; Lécuyer, Eric (Frontiers in Microbiology, 2017)
In the evolutionary arms race, symbionts have evolved means to modulate each other’s physiology, oftentimes through the dissemination of biological signals. Beyond small molecules and proteins, recent evidence shows that small RNA molecules are transferred between organisms and transmit functional RNA interference signals across biological species. However, the mechanisms through which specific RNAs are sorted for secretion and protected from degradation in the environment remain largely enigmatic. Over the last decade, extracellular vesicles have emerged as prominent vehicles of biological signals. They can stabilize specific RNA transcripts in biological fluids and selectively deliver them to recipient cells. Here, we review examples of small RNA transfers between plants and bacterial, fungal and animal symbionts. We also discuss the transmission of RNA interference signals from intestinal cells to populations of the gut microbiota, along with its roles in intestinal homeostasis. We suggest that extracellular vesicles may contribute to inter-species crosstalk mediated by small RNA. We review the mechanisms of RNA sorting to extracellular vesicles and evaluate their relevance in cross-species communication by discussing conservation, stability, stoichiometry and co-occurrence of vesicles with alternative communication vehicles.